2008
DOI: 10.1007/s10350-008-9230-7
|View full text |Cite
|
Sign up to set email alerts
|

Anal Resting Pressures at Manometry Correlate with the Fecal Incontinence Severity Index and with Presence of Sphincter Defects on Ultrasound

Abstract: Patients with and without sphincter defects had similar severity scores, but patients with defects had a significant decrease in resting pressures. Patients with larger sphincter defects had lower severity scores and resting pressures. Until a manometry cutoff can be set to discriminate between absence and presence of defects, both manometry and ultrasound should be offered to patients with history of anal trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 21 publications
5
20
1
Order By: Relevance
“…Although our results show no differences in continence scores between patients with and without symptoms and no correlation between muscle length, scores, and squeezing pressure as measured by anorectal manometry, we did observe a positive correlation between resting pressure and anterior EAS and IAS length on 3-DAUS in patients who had sphincter defects. These results are consistent with those of previous studies (2,22) , but all these measurements are relevant to therapeutic decision making, as ultrasound can differentiate between incontinent patients with intact anal sphincters and those with sphincter lesions, as well as associate anal pressures and symptoms, providing additional value to select patients for different treatment modalities. Fecal incontinence is multifactorial; different mechanisms are involved (12) and patients with fecal incontinence and intact sphincter may have muscle degeneration, atrophy, or pudendal neuropathy (19,23,25) .…”
Section: Eas Defect Plus Eas + Ias Defect (N = 33) Anterior Ias (Cm) Vssupporting
confidence: 91%
See 1 more Smart Citation
“…Although our results show no differences in continence scores between patients with and without symptoms and no correlation between muscle length, scores, and squeezing pressure as measured by anorectal manometry, we did observe a positive correlation between resting pressure and anterior EAS and IAS length on 3-DAUS in patients who had sphincter defects. These results are consistent with those of previous studies (2,22) , but all these measurements are relevant to therapeutic decision making, as ultrasound can differentiate between incontinent patients with intact anal sphincters and those with sphincter lesions, as well as associate anal pressures and symptoms, providing additional value to select patients for different treatment modalities. Fecal incontinence is multifactorial; different mechanisms are involved (12) and patients with fecal incontinence and intact sphincter may have muscle degeneration, atrophy, or pudendal neuropathy (19,23,25) .…”
Section: Eas Defect Plus Eas + Ias Defect (N = 33) Anterior Ias (Cm) Vssupporting
confidence: 91%
“…Recent advances in technology and the advent of three-dimensional ultrasonography have enabled multiplanar study of anal canal anatomy and measurement of the length and volume of the anal canal muscles (22,27) . Although some studies have reported poor correlation between symptoms, anal manometry pressures, and ultrasound measurements (4,5,22) , both studies should be offered to symptomatic patients (2) . A wide range of treatment modalities is available, including biofeedback, surgical sphincter repair, sacral nerve stimulation, and the artificial bowel sphincter, and a comprehensive assessment is required to identify anatomic and functional changes and inform the choice for the best treatment option.…”
Section: Introductionmentioning
confidence: 99%
“…Bordeianou et al [38] observed a correlation between MRP and severity, while Osterberg et al [22] found a correlation between MSP and severity. No correlation between severity and the pressure values was reported by Penninckx et al [24].…”
Section: Discussionmentioning
confidence: 99%
“…More treatment options for FI makes a proper pretreatment evaluation increasingly important, whether by means of subjective severity questionnaires, such as the FISI, or by objective measurements, such as ARM, anal endosonography, electromyography, and defecography [1]. Bordeianou et al [5] reported MRP was the only objective measurement that seems to correlate with both FISI and the presence of sphincteric defects on anal endosonography, while maximal squeeze pressure (MSP) generated by the EAS was not correlated. Our results confirm a strong association between low MRP and FI.…”
Section: Open Accessmentioning
confidence: 99%
“…The IAS contributes an estimated 55% -85% to maximal resting pressure (MRP) [3,4]. Low MRP is the most important predictor of FI and correlates with the Fecal Incontinence Severity Index (FISI) [5].…”
Section: Introductionmentioning
confidence: 99%